G168(P) A case of kocher-debre-semelaigne syndrome associated with renal dysfunction. (24th May 2017) - Fordham, J; Kumar, Y; Aamir, T
Abstract : A case is presented of a 14 year old boy referred to Paediatric outpatient clinic with elevated creatinine found on investigation for leg muscle cramping particularly on exertion. Further history uncovered reduced activity, poor appetite, daytime sleepiness and constipation for around 2 years duration. Examination revealed typical facial and body habitus of a child with longstanding severe hypothyroidism. There was also marked hypertrophy of the calf muscles. Blood tests showed elevated TSH (>100 mIU/L), repressed T3 and T4 (0.3 mcg/dL), elevated creatine kinase (5378 IU/L) and elevated thyroid peroxidase antibodies (41.7 IU/ mL). Treatment with thyroxine was commenced based on a diagnosis of Kocher-Debre-Semelaigne syndrome. This is an association of hypothyroidism and muscular pseudohypertrophy seen in childhood. The underlying thyroid defect can vary from acquired (autoimmune, as in this case) to congenital. As such the syndrome, though rare worldwide, is significantly more so in countries that screen for congenital hypothyroidism 1 . At presentation, features of hypothyroidism are usually florrid and complications such as acute compartment syndrome and rhabdomyolysis may occur 2 . To our knowledge renal dysfunction in association with this syndrome has never been reported out of the context of these complications. Muscle biopsy is rarely necessary. The muscular pseudohypertrophy and clinical features of hypothyroidism revert with treatment of the hypothyroidism, though final height may still be reduced.